HUBUNGAN ANTARA PENGETAHUAN DAN PELATIHAN ASUHAN PERSALINAN NORMAL (APN) DALAM PELAKSANAAN STANDAR ASUHAN PERSALINAN NORMAL (APN) - Sari, Intan (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
World Health Organization (WHO) estimates that more than 585 000 women per year died from childbirth. The maternal mortality rate (MMR) in 2012 according to SDKI amounted to 317 per 100,000 live births. Care of normal deliveries  is a clean and safe care during labor and  After birth and prevention of complications, especially post-partum bleeding, hypothermia and asphyxia, newborn. This study aims to determine the relationship between knowledge and training of midwives Care of normal deliveries  with the implementation of the standard normal delivery care in health centers Private Practice Midwive Cambai Prabumulih working area 2017. The design of this study is analytical survey with Cross Sectional approach. The population in this study were all midwives in Private Practice Midwives (CPM) Cambai health center Prabumulih working area of ​​2017 amounted to 30 and using purposive sampling. This research instrument used questionnaires and check list. Data analysis was performed by univariate and Bivariate. The results of this study show from 30 midwives who did not get in the implementation of the standard of care of normal deliveries 16 people (53.3%), which have less knowledge of as many as 17 people (56.7%) midwives, who did not care labor training as many as 20 people (66.7%). The results of bivariate analysis using Chi square test statistic that compares the p value with the significance level α (0.05) of the incident which showed  relationship between knowledge Midwives where p value = 0.001, and significant relationship between normal birth care training  with the implementation of the standard of care of normal deliveries in which the p value = 0.019. Health workers in particular are advised to keep improving the processing Midwives Midwives against predetermined standards in the care of normal deliveries. Keywords : Implementation of the normal standard of care delivery (APN)